Rodrigo Polanco, Hans Urs von Balthasar I. Ejes estructurantes de su teología, Madrid: Ediciones Encuentro, 2021, 360 pp. + IV, ISBN: 978-84-1 339-063-5. - Espezel, Alberto (2021)
Fil: Espezel, Alberto. Pontificia Universidad Católica Argentina; Argentina